IMAGING DIAGNOSIS—USE OF RADIOGRAPHY AND COMPUTED TOMOGRAPHY IN THE DIAGNOSIS OF A MINERALIZED YOLK SAC IN A BROWN KIWI (APTERYX MANTELLI). Issue 4 (9th September 2014) - Wightman, Paul; Cohen, Eli B.; Hunter, Stuart; Gartrell, Brett
<x xml:space="preserve">Abstract</x> A 12‐day‐old Brown Kiwi (Apteryx mantelli) was presented with anorexia, torticollis, head‐tilt, and coelomic distension. Radiographs showed an ill‐defined, fat‐opaque, coelomic mass displacing viscera craniodorsally. Curvilinear mineral opacities were superimposed over the ventral aspect of the mass. Computed tomography demonstrated the presence of mineral within the periphery of a fat attenuating mass consistent with a retained yolk sac. A deutectomy (yolk sac excision) was performed. Histopathology of the excised tissue confirmed the diagnosis of a retained yolk sac with multifocal mineralization.